A importância das parcerias na educação profissional - Martino, Mariluci Alves (2006)
The fast development of news technologies and comunication has caused deep changes in the economical, political and social context. In this new pattern of global competition, the capacity of bringing up innovations as soon as possible is extremely important. The education regarded within this context involves, on one hand, the improvements brought by the introduction of moderns technologies of information and communication and on the other hand, the need to advance the process of social inclusion and to think over the relation between education and labor. Technological innovations have changed the aspect of work and job; the global environment has brought a new view on the companies and management strategies like temporary jobs, outsourcing, virtual companies, international projects, on-line work, etc. So, the professional activity has got an universal characteristic, extending the social dimension of its meaning since a lot of professionals have no longer performed in a local job market, but in a global one. The professional education has felt these new changes much faster. So, its challenge is to keep pace with new jobs and respond to the need for work specialization. Under this perspective, the partnership practice may help school develop its social task and also review its management procedures. The purpose of the present work is to analyze, based on experience, the main impacts of partnership practice developed by professional schools of Centro Estadual de Educação Tecnológica Paula Souza as well as the potential changes in professional education. The main point is that the changes must be made in an articulated way, since the education results are of general interest. Therefore, articulating education with other agents that must show great competence tends to generate a positive impact on the system as a whole. In a way, it is said that the actions of educational policies have to be taken in a large, systemic and integrated context, which will affect the partnership practice involving public and private, economical, social and cultural agents. The bottom line is that the partnership practice is still slow, specially when it results from a larger proposition of integrated and sustainable local development. However, the participants of this research showed that the partnership practice responds to social changes and it is a way to face the new reality in which each segment is still trying to adjust and define its respective role